Formulation of a Lip Cream Containing Asoka Flower Extract (Ixora Javanica (Blume) DC.) as a Natural Colorant - Dea Dayana; Kartika Sari (Jurnal Indonesia Sosial Sains, 2026)
Lip cream is a lip coloring product in the form of a semi-solid or cream. The composition of lip cream is similar to decorative cosmetics in general, which consists of active ingredients in the form of dyes in various basic ingredients or bases. This study aims to develop a formula for herbal lip cream preparations from asoka flower extract (Ixora javanica (Blume) DC.) and provide information about evaluation tests in the form of lip cream preparations. This research began with asoka flower extract using the maceration method with 96% ethanol solvent. The extract is made into lip cream preparations with the formulas 1,2 and 3, using the melting and mixing method. The lip cream produced is evaluated and tested for stability which includes organoleptic observation, homogeneity test, pH test, dispersion test, adhesion test, application power test, and determination of the type of lip cream. The results of the physical evaluation showed that the F0, F1, F2 and F3 lip creams met the requirements for physical stability. Based on the results of the study, it can be concluded that asoka flower extract can be formulated into lip cream preparations.